1-(3,5-Dimethoxyphenyl)-2-(4-fluorophenyl)-4,5-dimethyl-1H-imidazole - Rosepriya, S. (International Union of Crystallography, 2012)
In the title compound, C(19)H(19)FN(2)O(2), the imidazole ring is essentially planar [maximum deviation = 0.0030 (8) Å] and makes dihedral angles of 66.45 (7) and 29.98 (7)° with the benzene rings attached to the ring N and C atoms, respectively. The dihedral angle between the two benzene rings is 64.79 (7)°. A C—H⋯π interaction is found in the crystal structure. The two methoxy groups were found to be disordered over two sets of sites with occupancy factors of 0.803 (4) and 0.197 (4). The F atom is disordered over two sites with occupancy factors of 0.929 (4) and 0.071 (4).